Fatigue behaviour analysis of AISI 316-L parts obtained by machining process and additive manufacturing. Issue 1 (October 2021) - Bermudo, C; Trujillo, F J; Martín, S; Herrera, M; Sevilla, L
Abstract: Due to the great technological growth, 3D printing is becoming of great relevance within the automotive, aerospace and even medicine sectors. With this manufacturing method, parts with a complex geometry can be manufacture with considerable time and material savings compared to traditional processes such as machining. However, additive manufacturing processes still have a series of unresolved problems. Present work makes a comparison between AISI 316-L samples obtained by Selective Laser Melting technique and Dry Machining. The comparison is focus in properties mainly relevant in the industrial sectors highlighted. Macro and microgeometrical deviations, such as roughness, roundness and straightness are obtained in each case study and compared. Results show that, although for the printed samples the material deposition direction plays a fundamental role, being the horizontal samples the ones with better results due to the direction of the layers, the machining process is the one with significant better results compared to the 3D printing process. After the macro and microgeometrical deviations measurements, all samples were subjected to a rotational bending fatigue test for a mechanical behaviour study. As expected, the mechanized specimens have a better fatigue behaviour due to the better surface finish, among other aspects. Between the additive manufactured specimens, the vertical is the one that presents a better behaviour due to the transverse orientation of the deposited layers.